Repressing the effects of variable speed harmonic orders in operational modal analysis. (15th October 2016) - Randall, R.B.; Coats, M.D.; Smith, W.A.
Abstract: Discrete frequency components such as machine shaft orders can disrupt the operation of normal Operational Modal Analysis (OMA) algorithms. With constant speed machines, they have been removed using time synchronous averaging (TSA). This paper compares two approaches for varying speed machines. In one method, signals are transformed into the order domain, and after the removal of shaft speed related components by a cepstral notching method, are transformed back to the time domain to allow normal OMA. In the other simpler approach an exponential shortpass lifter is applied directly in the time domain cepstrum to enhance the modal information at the expense of other disturbances. For simulated gear signals with speed variations of both ±5% and ±15%, the simpler approach was found to give better results The TSA method is shown not to work in either case. The paper compares the results with those obtained using a stationary random excitation. Highlights: Two cepstral methods for removal of variable speed harmonic orders compared. TSA shown not to work with speed variations of the order of 5–15%. Exponential liftering in time domain better than notch liftering in order domain. After cepstral lifter pre-processing, response signals produce good OMA results. OMA results compared with those for excitation by stationary random noise.